The Pre-Removal Detention of Immigrants: A Return to Ordinary Meaning - Bas Schotel; Ingo Venzke (German Law Journal)
The EU Return Directive demands that immigrant detention be as short as possible, but, by logical implication, this also means that detention can be as long as necessary. What concerns the maximum length of detention, the Return Directive is remarkably generous: Immigrants can be detained for a period of up to eighteen months—a deprivation of liberty that is otherwise justified only as punishment for serious crimes. The practice of such long-term detention, now burgeoning, is highly questionable for moral, practical, and—our focus—legal reasons.